INFORMATION MANAGEMENT ZN GOVERNMENTAL PROCEDURES - Adem Öğüt (Selçuk Üniversitesi Sosyal Bilimler Meslek Yüksekokulu Dergisi)
In the contemporary organizational world, information manage-ment and management information systems are interdependent. Management information Systems (MİS) plays a strategic role in effective information management as well as organizational management in general. An MİS formally organizes the information managers need to plan the future course of an organizatiön and to make decisions on the optimal allocation of organizational resources. Ali governmental departments are concerned with information, vvhether as sources of information, as agencies in charge of information management or information utilization. In governmental procedures, obtaining and ma-naging information by itself doesn't guarantee organizational success and the nature of public management is different from that of private management. As a result, a comprehensive Public Management Information Systems (PMIS) considering external control and sensitivity to political change should be developed in terms of governmental institutions.